A conceptual model of northern midlatitude tropospheric ozone. Issue 6 (13th September 2022) - Mims, Charles A.; Parrish, David D.; Derwent, Richard G.; Astaneh, Mohammad; Faloona, Ian C.
Abstract : The average (climatic) seasonal pattern of ozone in the northern mid-latitude troposphere is explained by a very simple model. Reference to such basic models is a valuable tool for the interpretation of complex simulations and measurements. Abstract : A simple compartmental model is used to simulate the average (climatic) annual and seasonal distribution of ozone in the Northern Hemisphere midlatitude troposphere. The model (reminiscent of earlier examples) consists of a circular set of segments – 4 marine and 5 continental – which span the globe. Each segment consists of two well-mixed compartments, one representing the free troposphere overlying one representing the boundary layer. A minimal set of parameters with values taken from generally accepted and measured behavior is used to describe the ozone sources and sinks within the segments and inter-compartmental flow and mixing. The model accurately simulates measured seasonal cycles of ozone throughout the midlatitude troposphere. By virtue of relatively rapid circular zonal flow the model reproduces the observed nearly uniform free troposphere that behaves as a reservoir, responding to the combined boundary layer and stratospheric inputs. The distinctive seasonal cycles of the free troposphere and the marine boundary layer are well reproduced by the strong seasonal dependence of the loss mechanism initiated by ozone photolysis that yields O 1 D. The critical role of the marine boundary layer in the global ozone balance and the constraints that it places on the net continental production are clearly revealed. Sensitivity analysis identifies which of the basic set of process parameters most require better understanding. Minimalist models such as this, used in conjunction with detailed CTM model simulations, can help provide a comprehensive understanding of the climatic behavior and trends in tropospheric ozone.